2009
DOI: 10.1007/s00122-009-1230-z
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of clubroot resistance in radish (Raphanus sativus L.)

Abstract: A QTL analysis for clubroot resistance (CR) of radish was performed using an F(2) population derived from a crossing of a CR Japanese radish and a clubroot-susceptible (CS) Chinese radish. F(3) plants obtained by selfing of F(2) plants were used for the CR tests. The potted seedlings were inoculated and the symptom was evaluated 6 weeks thereafter. The mean disease indexes of the F(3) plants were used for the phenotype of the F(2). The results of two CR tests were analyzed for the presence of QTL. A linkage ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 35 publications
0
56
0
Order By: Relevance
“…However, efforts to use these markers in oat have not yet produced a consensus map, in which all linkage groups are assigned to the expected 21 oat chromosomes. AFLP markers have been associated with resistance genes in several species, including wheat (Weng and Lazar 2002;Randhawa et al 2009), tomato (Giovanni et al 2004;Golas et al 2010), maize (Duble et al 2003;Chen et al 2004;Liu et al 2009), canola (Kaur et al 2009), and radish (Kamei et al 2010). In the present study, the AFLP molecular markers U8PM22 and U8PM25, developed by Locatelli et al, were associated with the Pc68 gene.…”
Section: Mapping Analysismentioning
confidence: 99%
“…However, efforts to use these markers in oat have not yet produced a consensus map, in which all linkage groups are assigned to the expected 21 oat chromosomes. AFLP markers have been associated with resistance genes in several species, including wheat (Weng and Lazar 2002;Randhawa et al 2009), tomato (Giovanni et al 2004;Golas et al 2010), maize (Duble et al 2003;Chen et al 2004;Liu et al 2009), canola (Kaur et al 2009), and radish (Kamei et al 2010). In the present study, the AFLP molecular markers U8PM22 and U8PM25, developed by Locatelli et al, were associated with the Pc68 gene.…”
Section: Mapping Analysismentioning
confidence: 99%
“…napobrassica) (Ayers and Lelacheur 1972;Gustafsson and Fa¨lt 1986). Most radish (Raphanus sativus L.) cultivars and lines are also known to be resistant to the clubroot pathogen (Kamei et al 2010).…”
mentioning
confidence: 99%
“…Yoshikawa (1981) reported that CR of European fodder turnips was controlled by a major gene in addition to some minor genes. By QTL analysis, Kamei et al (2007) indicated that CR of radish was also controlled by a major gene and some minor genes. In addition, Suwabe et al (2006) reported that two loci for clubroot resistance (Crr1 and Crr4) were expressed against the Ano-01 isolate in B. rapa.…”
Section: Resultsmentioning
confidence: 99%
“…However, the CR gene(s) of radish has not been investigated in comparison with that of Brassica crops such as B. rapa (2n = 20, AA), B. oleracea (2n = 18, CC), and B. napus (Kuginuki et al 1997, Moriguchi et al 1999, Manzanares-Dauleux et al 2000, Suwabe et al 2003, 2006, Hirai et al 2004, Nomura et al 2005. Although QTL analysis was conducted previously by Kamei et al (2007), the clubroot resistance of radish has not been investigated at the chromosomal level.…”
Section: Introductionmentioning
confidence: 99%